Upgrading strategies for effective utilization of biogas - Salihu, Aliyu; Alam, Md Zahangir (Wiley, 2015)
Production of biogas is based on anaerobic digestion of different renewable raw materials including human, animal, agricultural, industrial, and municipal wastes. In addition to methane content, biogas contains carbon dioxide along with water vapor, hydrogen sulfide, ammonia, and depending on the raw materials siloxane can be present. Thus, different purification and upgrading strategies are necessary in order to enhance the methane content; this review presents some of the upgrading technologies for practical removal of major contaminants in biogas. Recent development in membrane technology with high selectivity and permeability could serve as a boost in search for the most efficient biogas upgrading process capable of meeting the requirements for its use in vehicle fuel as well as incorporation in the natural gas grid.